Attitudinal Resources of the "Yellowface" (2023) Reviews on Goodreads: A Systemic Functional Linguistics Study - Zakiya Rodliya; Eva Tuckyta Sari Sujatna (Journal of Language and Literature, 2025)
The meaning of the language used in reviews can be evaluated using the attitudinal resources within the appraisal system proposed by Martin White in 2005. The framework provides the attitude subsystem that helps identify the clauses in the categories of Affect, Judgement, and Appreciation. This research aims to examine the attitudinal resources that occurred in the reviews of the "Yellowface" (2023) novel by Rebecca F. Kuang on the Goodreads website and how the reviewers' attitudes are expressed. This research used a qualitative descriptive method. The data was taken from the Goodreads website based on the top five popular reviews. After analyzing the clauses in the collected data, the researcher then classified them into three categories of attitudinal resources. From the 169 clauses that were identified, the results show that both positive and negative features and all resources occurred in the reviews, with Appreciation being the highest resource that is used, followed by Judgement and Affect. Based on the findings, this research argues that the reviewers tend to evaluate the book's content more than to judge the behavior of the author and the book's characters or to express their emotions concerning the book. As a result, the use of Appreciation might help other readers know the values and qualities of the book.